From emotion to meaning: A teaching application of Topic Theory in Musicology - Pedrero-Encabo, Águeda; Díaz-Emparanza, Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This innovation project aims to correct the difficulties of students of the Degree in Musicology to use musical analysis tools. It is oriented towards the curricular competences of the subject Music and Thought in the Age of Enlightenment (18th century). This requires analytical work on the Central European tonal music repertoire in connection with the currents of style and thought of the time. According to the principle of Topic theory, a series of didactic strategies have been developed in order to connect the emotional experience of the student with the meaning of musical topics.